Security operations centers in information technology and operational technology environments: A literature review of requirements, differences, issues, and improvements of IT and OT SOC environments - Havi, Lauri (My University, 2025)
A growing trend that is increasingly spreading in industries that rely on both information technology and operational technology systems to drive digital transformation is the convergence of both domains. The convergence of information technology and operational technology presents both opportunities and challenges for organizations. While this convergence enables automation, data analytics, and improved efficiency, it also creates a complex security landscape where traditional information technology security measures are often inadequate. This research focuses on the information technology and operational technology security operations centers by first comparing them as separate entities, and finally studying the emerging concept of converged security operations centers, where one security operations center maintains security operations for both information technology and operational technology environments. This study aims to understand the common requirements, differences, issues, and improvements of security operations centers in both information technology and operational technology environments. The research conducts a comprehensive literature review of existing research and industry reports to analyze the requirements and differences between information technology and operational technology security operations centers, identify key issues, and explore improvements for implementing effective information technology and operational technology security operations centers. This analysis aims to create a holistic view of the current landscape of the state of the security operations centers in both environments. After that, based on the results, the concept of converged security operations centers is studied to determine whether this model is possible and what potential benefits or drawbacks it brings to the organizations using this model. The research reveals that the unique characteristics of information technology and operational technology environments necessitate distinct approaches to security monitoring, incident response, threat intelligence gathering, regulatory compliance, and personnel training. The review identifies key requirements for successful both information technology and operational technology security operations centers, highlighting the importance of specialized expertise, communication & collaboration with external teams & specialists, robust security tools, integrated security processes, and strong governance frameworks. The findings emphasize the need for a comprehensive approach to managing information technology and operational technology security, recognizing the interconnected nature of these environments and the potential for attacks to spread between them. The research concludes with recommendations for organizations seeking to establish or enhance their converged security operations center capabilities, stressing the importance of collaboration, ongoing training, and the continuous adaptation of security strategies to address evolving threats. Kasvava trendi, joka leviää yhä enemmän eri toimialoilla, jotka tukeutuvat sekä tietotekniikkaan, että operatiivisen teknologian järjestelmiin digitaalisen muutoksen edistämiseksi, on molempien ympäristöjen läheneminen. Tietotekniikan ja operatiivisen teknologian läheneminen tarjoaa organisaatioille sekä mahdollisuuksia että haasteita. Vaikka tämä läheneminen mahdollistaa automaation, data-analytiikan ja tehokkuuden parantamisen, se luo myös monimutkaisen turvallisuusympäristön, jossa perinteiset tietoturvan toimenpiteet ovat usein riittämättömiä. Tämä tutkimus keskittyy tietotekniikan ja operatiivisen teknologian tietoturvakeskuksiin vertaa-malla niitä ensin erillisinä yksiköinä ja lopuksi tutkimalla kasvavaa yhdistettyjen tietoturvakeskusten käsitettä, jossa yksi tietoturvakeskus ylläpitää tietoturvaa sekä tietotekniikan että operatiivisen teknologian ympäristöissä. Tämän tutkimuksen tavoitteena on ymmärtää tietoturvakeskusten yhteisiä vaatimuksia, eroja, ongelmia ja parannuksia sekä tietotekniikan että operatiivisen teknologian ympäristöissä. Tutkimuksessa tehdään kattava kirjallisuuskatsaus olemassa oleviin tutkimuksiin ja alan raportteihin analysoidakseen tietotekniikan ja operatiivisen teknologian tietoturvakeskusten vaatimuksia ja eroja, tunnistaakseen keskeiset haasteet ja tutkiakseen parannuksia tehokkaiden tietotekniikan ja operatiivisen teknologian tietoturvakeskusten toteuttamiseksi. Tämän analyysin tavoitteena on luoda kokonaisvaltainen kuva molempien ympäristöjen turvallisuusoperaatiokeskusten nykytilasta. Tämän jälkeen tulosten perusteella tutkitaan yhdistettyjen tietoturvakeskusten käsitettä sen määrittämiseksi, onko tämä malli mahdollinen ja mitä mahdollisia hyötyjä tai haittoja se tuo mallia käyttäville organisaatioille. Tutkimus paljastaa, että tietotekniikan ja operatiivisten teknologian ympäristöjen ainutlaatuiset ominaisuudet edellyttävät erilaisia lähestymistapoja tietoturvan seurantaan, tapahtumiin reagointiin, uhkien tiedonkeruuseen, sääntelyiden noudattamiseen ja henkilöstön koulutukseen. Katsauksessa tunnistetaan sekä tietotekniikan että operatiivisten teknologian tietoturvakeskusten menestyksekkään toiminnan keskeiset vaatimukset korostaen erikoisosaamisen, ulkoisten tiimien ja asiantuntijoiden kanssa tapahtuvan viestinnän ja yhteistyön, vankkojen tietoturvatyökalujen, integroitujen tietoturvaprosessien ja vahvojen hallintokehysten merkitystä. Tulokset korostavat kokonaisvaltaisen lähestymistavan tarvetta tietotekniikan ja operatiivisen teknologian turvallisuuden hallintaan, tunnustaen näiden ympäristöjen toisiinsa kytkeytyneen luonteen ja hyökkäysten leviämismahdollisuuden niiden välillä. Tutkimus päättyy suosituksiin organisaatioille, jotka pyrkivät luomaan tai parantamaan yhdistetyn tietoturvakeskusten valmiuksiaan, korostaen yhteistyön, jatkuvan koulutuksen ja tietoturvastrategioiden jatkuvan mukauttamisen merkitystä kehittyvien uhkien torjumiseksi.
Keywords: fi=Tietojärjestelmätiede|en=Information Systems|; fi=Tietojärjestelmätieteen maisteriohjelma|en=Master’s Programme in Information Systems|